1997
DOI: 10.1136/vr.140.23.606
|View full text |Cite
|
Sign up to set email alerts
|

Commercial polyester fabric repair of abdominal hernias and defects

Abstract: The Veterinary Formulary The third edition of The Veterinary Formulary, published by the British Veterinary Association and the Royal Pharmaceutical Society of Great Britain, is available in a new, larger format and has been extensively revised. The formulary is available, price £52, overseas £55, from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
5

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
1
7
0
5
Order By: Relevance
“…Adhesions between the reconstructed site and intraperitoneal organs after hernioplasty with different prosthetic materials have been reported 15,44 . Uniform covering of prosthetic material with a layer of white connective tissue of variable thickness, as seen in the present study, was also observed by Shoukry 36 .…”
Section: Discussionsupporting
confidence: 72%
“…Adhesions between the reconstructed site and intraperitoneal organs after hernioplasty with different prosthetic materials have been reported 15,44 . Uniform covering of prosthetic material with a layer of white connective tissue of variable thickness, as seen in the present study, was also observed by Shoukry 36 .…”
Section: Discussionsupporting
confidence: 72%
“…This is due to a greater availability of polypropylene mesh, is one of the most well studied techniques and most commonly used to solve the problem (SHOUKRY, 1997). There are few studies concerning different types of biological materials, making many professional no longer play, despite the increasing number of procedures performed with these materials both in human and veterinary medicine (OLIVEIRA et al, 2009;SINGH et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic and biological materials can be used as prosthesis for the repair of large abdominal wall defects. The different synthetic materials used are polyester fabric (Shoukry et al, 1997), nylon, Dacron and stainless steel (Kanade et al, 1988;George and Mohammad, 1993), cotton mesh (Kanade and Kumar,1990), mosquito net mesh (Stephenson and Kingsnorth, 2011), vicryl mesh (Buchsbaum et al, 1985), polypropylene mesh (Kassam et al, 2014), expanded polytetrafluro ethylene (PTFE) (Kennedy and Matyas, 1999;Gillion et al, 1999), mersilene mesh (Riply and Mc Carnon,1994), Carbon fibers and Carbon sheet (Gangwar, 2002), oxidized generated cellulose, polyethylene glycol and hylan G-F20 (Altinli et al, 2011). A synthetic nonabsorbable material Polypropylene mesh (PP), is the most widely used material for abdominal wall replacement and reinforcement during hernia repair (Bastos et al, 2006).…”
Section: Prosthesis In Hernia Repairmentioning
confidence: 99%